An exploratory survey regarding the Maryland Contraceptive Equity Act: clinician awareness and impact on contraception provision - Aneesha Cheedalla; Jessica K. Lee; Anne E. Burke (Elsevier, 2022)
Objective: The Maryland Contraceptive Equity Act took effect in January 2018 with the goal of reducing insurance barriers to contraception. We sought to assess the Act's impact on contraceptive provision. Study Design: From March-August 2019, we emailed an exploratory survey to clinicians providing contraception in Maryland that queried awareness of the Act and changing practices. Results: The survey had a 13% response rate (164/1256 clinicians). Fifty (31%) were aware of the Act. Clinicians rated the Act was somewhat likely to change prescribing practices (3.5/5 point Likert Scale, SD 1.3). Conclusion: The majority of clinicians providing contraception in Maryland are not aware of the Act. If aware of the Act, clinicians may change their contraceptive prescribing practices.